Marriage and wages - Elena Bardasi; Mark P. Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2005)
This work investigates the commonly observed relationship between marriage and wages among men in Britain using panel data covering the 1990s. We explicitly test several hypotheses developed in the literature to explain this relationship, including the household division of labour and specialisation, differential rates of human capital formation, employer favouritism, and self-selection. After accounting for individual-specific time-invariant effects, and a wide range of individual, household, job and employer related characteristics, we find a small but statistically significant premium remains that can be attributed to productivity differences. Our estimates provide evidence for the existence of a large selection effect into marriage based on both observable and unobservable characteristics that are positively correlated with wages (consistent with employers using marriage as a positive signal), and also evidence in support of the specialisation hypothesis.
Keywords: 330